Cellular Behaviour in Root Meristem Cells of Zinnia Elegans in Vivo and in Tissue Culture Systems - Mat Taha, Rosna; Othman, Rashidi (Malaysian Journal of Science, 2002)
Zinnia elegans is an attractive ornamental plant imported from overseas. Tissue culture of this species is beneficial for mass propagation, especially for commercial purposes. In this paper, we report on cellular studies of this species which is rarely done. Cellular parameters such as Mitotic Index (MI), chromosomes counts, ploidy level/nuclear DNA content, cell doubling time (Cdt) and measurement of mean cell and nuclear areas were recorded from root meristem cells grown in vivo and roots cultured in vitro. In this study, we have found that in vitro root under short term culture, showed an increase in the MI value, the chromosome number remained stable, the mean cell and nuclear areas decreased, the polyploid cells increased slightly, more cells entering S phase of the cell cycle and the duration of Cdt shortened in vitro. These behaviour are consistent with the readiness of this species to regenerate in vitro and the long term culture confirmed this observation and the regenerants obtained were true to type.Zinnia elegans is an attractive ornamental plant imported from overseas. Tissue culture of this species is beneficial for mass propagation, especially for commercial purposes. In this paper, we report on cellular studies of this species which is rarely done. Cellular parameters such as Mitotic Index (MI), chromosomes counts, ploidy level/nuclear DNA content, cell doubling time (Cdt) and measurement of mean cell and nuclear areas were recorded from root meristem cells grown in vivo and roots cultured in vitro. In this study, we have found that in vitro root under short term culture, showed an increase in the MI value, the chromosome number remained stable, the mean cell and nuclear areas decreased, the polyploid cells increased slightly, more cells entering S phase of the cell cycle and the duration of Cdt shortened in vitro. These behaviour are consistent with the readiness of this species to regenerate in vitro and the long term culture confirmed this observation and the regenerants obtained were true to type.Zinnia elegans is an attractive ornamental plant imported from overseas. Tissue culture of this species is beneficial for mass propagation, especially for commercial purposes. In this paper, we report on cellular studies of this species which is rarely done. Cellular parameters such as Mitotic Index (MI), chromosomes counts, ploidy level/nuclear DNA content, cell doubling time (Cdt) and measurement of mean cell and nuclear areas were recorded from root meristem cells grown in vivo and roots cultured in vitro. In this study, we have found that in vitro root under short term culture, showed an increase in the MI value, the chromosome number remained stable, the mean cell and nuclear areas decreased, the polyploid cells increased slightly, more cells entering S phase of the cell cycle and the duration of Cdt shortened in vitro. These behaviour are consistent with the readiness of this species to regenerate in vitro and the long term culture confirmed this observation and the regenerants obtained were true to type.Zinnia elegans is an attractive ornamental plant imported from overseas. Tissue culture of this species is beneficial for mass propagation, especially for commercial purposes. In this paper, we report on cellular studies of this species which is rarely done. Cellular parameters such as Mitotic Index (MI), chromosomes counts, ploidy level/nuclear DNA content, cell doubling time (Cdt) and measurement of mean cell and nuclear areas were recorded from root meristem cells grown in vivo and roots cultured in vitro. In this study, we have found that in vitro root under short term culture, showed an increase in the MI value, the chromosome number remained stable, the mean cell and nuclear areas decreased, the polyploid cells increased slightly, more cells entering S phase of the cell cycle and the duration of Cdt shortened in vitro. These behaviour are consistent with the readiness of this species to regenerate in vitro and the long term culture confirmed this observation and the regenerants obtained were true to type.